Yeast Jhd2p is a histone H3 Lys4 trimethyl demethylase. - Liang, G; Klose, R; Gardner, K; Zhang, Y (2007)
Histone methylation is important in regulating chromatin structure and function. In budding yeast, methylation of histone H3 at Lys4 (H3-K4) is associated with active transcription and is enriched at the 5' regions of transcribed genes. Here we identify a novel budding yeast JmjC domain-containing H3-K4 demethylase, Jhd2p, that antagonizes the trimethyl modification state and contributes to regulation of telomeric silencing.